Effect of sonic versus ultrasonic activation on aqueous solution penetration in root canal dentin - Dámaris Macías; Víctor Bravo; Diego Echeverría (Universidad de Concepción., 2018)
The aim of this study was to observe the penetration of an aqueous solution into the root canal dentin under sonic activation and ultrasonic activation. Materials and Method: This study consisted of experimental in vitro research. In order to achieve a closed system, the apex of 45 single-rooted teeth was sealed with wax. The step-back technique was manually performed using a K50 apical master file and 3 groups were organized according to the protocol of the final irrigant activation: Group I: non-activated Chinese ink for 30 seconds, Group II: Chinese ink sonically activated with EndoActivator for 30 seconds, and Group III: Chinese ink ultrasonically activated with Varios 350 equipment for 30 seconds. Teeth were sectioned longitudinally, and the samples obtained were observed under a stereomicroscope at 1X magnification in order to be photographed and scanned to calculate the penetration area using the Image J software. The tinted radicular area was evaluated in relation to the total area of the root dentin. The Tukey's post-hoc test and ANOVA were used for the statistical analysis (p<0.05). Results: Group I and II obtained 9.13% and 9.42% penetration respectively, while in group III the highest degree of dye infiltration was achieved (13.9%), being statistically significant (p<0.001). Conclusions: Ultrasonic activation produced a significantly higher penetration of the dye when compared to conventional activation and sonic activation.